Association between depression severity and fitness in in-patients with major depressive disorders - Kreppke, Jan-Niklas; Cody, Robyn; Gerber, Markus; Faude, Oliver (Current Issues in Sport Science (CISS), 2023)
Introduction It has been shown that people with major depressive disorder exercise less and have lower fitness levels than healthy individuals (Schuch et al., 2017). People with major depressive disorder have a decrease in their cardiovascular health which leads to a poorer autonomic function and heart rate variability (HRV; Kemp et al., 2010). However, not only objective parameters are influenced by major depressive disorder, but also subjective ones, like perceived fitness. As differences between people with major depressive disorder and healthy people have often been investigated, this study aims to investigate fitness, perceived fitness and HRV in individuals with different levels of depression severity. Methods The study is part of the multicentre randomised controlled PACINPAT trial, in which inpatients receive physical activity counselling. Data from baseline assessments are used for this analysis (Gerber et al., 2019). The classification according to depression severity is based on the Beck Depression Inventory (BDI-II). Fitness was determined using the submaximal Åstrand ergometer cycling test. Perceived fitness is self-reported and resting HRV was measured for 5 minutes. The three groups with different severity of depression were compared using ANCOVA for the three mentioned parameters. Results We analysed data from 215 patients. The average BDI-II score at baseline was 22.2 (SD 10.3; range 2-50). With regard to depression severity, 41.4% (n = 89) were classified as having mild depression, 34.4% (n = 74) presented with moderate depression, and 24.2% (n = 52) fell into the category of severe depression. Data analysis is not finalized yet. The presentation will focus on differences in terms of fitness, perceived fitness and HRV parameters between the three severity groups. Conclusion The study will show if there are differences in fitness, perceived fitness and autonomic function as measured by HRV between depressive patients of different severity levels. This complements previous research on differences between patients with major depressive disorder and healthy individuals. It may also help practitioners to tailor interventions more accurately to individuals with different levels of depression severity, as different levels of co-occurring symptoms need to be considered. References Gerber, M., Beck, J., Brand, S., Cody, R., Donath, L., Eckert, A., Faude, O., Fischer, X., Hatzinger, M., Holsboer-Trachsler, E., Imboden, C., Lang, U., Mans, S., Mikoteit, T., Oswald, A., Pühse, U., Rey, S., Schreiner, A.-K., Schweinfurth, N., . . . Zahner, L. (2019). The impact of lifestyle Physical Activity Counselling in IN-PATients with major depressive disorders on physical activity, cardiorespiratory fitness, depression, and cardiovascular health risk markers: Study protocol for a randomized controlled trial. Trials, 20(1), Article 367. https://doi.org/10.1186/s13063-019-3468-3 Kemp, A. H., Quintana, D. S., Gray, M. A., Felmingham, K. L., Brown, K., & Gatt, J. M. (2010). Impact of depression and antidepressant treatment on Heart Rate Variability: A review and meta-analysis. Biological Psychiatry, 67(11), 1067-1074. https://doi.org/10.1016/j.biopsych.2009.12.012 Schuch, F., Vancampfort, D., Firth, J., Rosenbaum, S., Ward, P., Reichert, T., Bagatini, N. C., Bgeginski, R., & Stubbs, B. (2017). Physical activity and sedentary behavior in people with major depressive disorder: A systematic review and meta-analysis. Journal of affective disorders, 210, 139-150. https://doi.org/10.1016/j.jad.2016.10.050